Debunking the Myth that Job Stress Has No Impact on Healthcare Performance: Membongkar Mitos bahwa Stres Kerja Tidak Berdampak pada Kinerja Pelayanan Kesehatan - Lutfiana Wahyu Maulida; Cholifah Cholifah (Academia Open, 2024)
This quantitative study examines the relationship between work stress and employee performance in 'Aisyiyah Siti Fatimah Tulangan Sidoarjo Hospital, focusing on a sample of 83 married employees selected through simple random sampling from a total population of 187. Utilizing Likert scales for data collection and simple linear regression analysis for data analysis, the research finds no significant effect of work stress on employee performance (p = 0.799, α = 0.05). These results suggest a potential gap in understanding this relationship within the hospital setting and highlight the need for comprehensive management strategies to address various factors influencing employee performance. The findings underscore the importance of further research to explore potential moderators and mediators and inform effective interventions for enhancing employee well-being and productivity in healthcare organizations. Highlights: 1. Examining work stress's impact on employee performance in healthcare.2. Quantitative study, 83 married employees sampled from total population.3. No significant effect found, highlighting need for comprehensive management strategies. Keywords: Work stress, Employee performance, Healthcare organizations, Quantitative research, Management strategies